MxA Mediates SUMO-Induced Resistance to Vesicular Stomatitis Virus - Maarifi, Ghizlane (J Virol, 2016)
Multiple cellular pathways are regulated by small ubiquitin-like modifier (SUMO) modification, including ubiquitin-mediated proteolysis, signal transduction, innate immunity, and antiviral defense. In the study described in this report, we investigated the effects of SUMO on the replication of two members of the Rhabdoviridae family, vesicular stomatitis virus (VSV) and rabies virus (RABV). We show that stable expression of SUMO in human cells confers resistance to VSV infection in an interferon-independent manner. We demonstrate that SUMO expression did not alter VSV entry but blocked primary mRNA synthesis, leading to a reduction of viral protein synthesis and viral production, thus protecting cells from VSV-induced cell lysis. MxA is known to inhibit VSV primary transcription. Interestingly, we found that the MxA protein was highly stabilized in SUMO-expressing cells. Furthermore, extracts from cells stably expressing SUMO exhibited an increase in MxA oligomers, suggesting that SUMO plays a role in protecting MxA from degradation, thus providing a stable intracellular pool of MxA available to combat invading viruses. Importantly, MxA depletion in SUMO-expressing cells abrogated the anti-VSV effect of SUMO. Furthermore, SUMO expression resulted in interferon-regulatory factor 3 (IRF3) SUMOylation, subsequently decreasing RABV-induced IRF3 phosphorylation and interferon synthesis. As expected, this rendered SUMO-expressing cells more sensitive to RABV infection, even though MxA was stabilized in SUMO-expressing cells, since its expression did not confer resistance to RABV. Our findings demonstrate opposing effects of SUMO expression on two viruses of the same family, intrinsically inhibiting VSV infection through MxA stabilization while enhancing RABV infection by decreasing IFN induction. IMPORTANCE We report that SUMO expression reduces interferon synthesis upon RABV or VSV infection. Therefore, SUMO renders cells more sensitive to RABV but unexpectedly renders cells resistant to VSV by blocking primary mRNA synthesis. Unlike the interferon-mediated innate immune response, intrinsic antiviral resistance is mediated by constitutively expressed restriction factors. Among the various anti-VSV restriction factors, only MxA is known to inhibit VSV primary transcription, and we show here that its expression does not alter RABV infection. Interestingly, MxA depletion abolished the inhibition of VSV by SUMO, demonstrating that MxA mediates SUMO-induced intrinsic VSV resistance. Furthermore, MxA oligomerization is known to be critical for its protein stability, and we show that higher levels of oligomers were formed in cells expressing SUMO than in wild-type cells, suggesting that SUMO may play a role in protecting MxA from degradation, providing a stable intracellular pool of MxA able to protect cells from viral infection.